The structures, water stabilities and photoluminescence properties of two types of iodocuprate(i)-based hybrids. Issue 7 (25th January 2018) - Liu, Guang-Ning; Zhao, Ruo-Yu; Xu, Hong; Wang, Zi-Han; Liu, Qi-Sheng; Shahid, Malik Zeeshan; Miao, Jin-Ling; Chen, Guozhu; Li, Cuncheng
Abstract : The effects of aromatic and aliphatic cations on the structure, water stability and photoluminescence of iodocuprate(i )-based materials were disclosed. Abstract : Although great progress has been made in hybrid iodocuprates(i ) as lighting phosphors, the effects of aromatic and aliphatic structure directing agents (SDAs) on their water stability, structure and photoluminescence (PL) properties are still not clear. Herein, aromatic N-heterocyclic 1, 2-di(4-pyridyl)ethylene (dpe), aliphatic N-heterocyclic 1, 8-diazabicyclo[5.4.0]undec-7-ene (dbu) and N -aminoethylpiperazine (app) were selected to be SDAs to construct two types of hybrid iodocuprates(i ) via a facile in situ approach. Aromatic dpe-derived cations are successfully directed to form (Me2 dpe)(CuI3 ) (1 ), (Me2 dpe) n (Cu4 I6 ) n (2 ), (Et2 dpe)2 (Cu6 I10 ) (3 ), and (H2 dpe) n (Cu2 I4 ) n (4 ). Three of them contain unprecedented inorganic iodocuprate clusters or chains. The aliphatic N-heterocyclic dbu- and app-derivative cations are responsible for the formation of (Hdbu) n (Cu2 I3 ) n (5 ) and (H3 app)2 (Cu2 I6 )·2I·2H2 O (6 ), which contain a (Cu2 I3 ) − chain and a (Cu2 I6 ) 4− binuclear cluster, respectively. For the first time, the influence mechanisms of the water stabilities of iodocuprate-based PL materials were disclosed, by analyzing the possible interactions between SDAs and water molecules.1–2 are PL silent due to their "self-quenching effect".3, 4 and 5 exhibit bright red, orange and yellow solid-state PL emissions at room temperature respectively, originating from the charge transfer between inorganic iodocuprate species and organic N-heterocycles. The co-template approach leads to multiple charge transfers in6, which features a tunable PL behavior from bluish green to white by varying the excitation light, and has a quantum yield up to 43% (the highest value among hybrid iodocuprates containing (Cu2 I6 ) 4− clusters). The comparative study not only helps us to rationally synthesize iodocuprate-based PL materials with enhanced performance, but also provides a new method to obtain wavelength-dependent PL materials.